Surgical interventions for chronic pelvic pain. Issue 4 (August 2016) - Senapati, Sangeeta; Atashroo, Diana; Carey, Erin; Dassel, Mark; Tu, Mark Frank F.
Abstract : Purpose of review: The objective of this study is to review an evidence-based approach to surgical treatment of key chronic pelvic pain (CPP) contributors emphasizing the importance of preoperative evaluation and counseling. Recent findings: CPP is a poorly understood but highly prevalent condition and there are limited, well constructed studies to guide effective, durable treatment. CPP arises from factors originating in multiple organ systems, including reproductive, urologic, gastrointestinal, and myofascial, all informing the central nervous system. For those with severe disabling conditions, who have a suboptimal response to medical management, surgical interventions can be offered for diagnostic evaluation and/or treatment. Leiomyoma, adenomyosis, adnexal disorder, pelvic adhesions, and pelvic varicosities are common considerations in the differential diagnosis of CPP amenable to surgical approach. Summary: Surgical treatments of CPP range from conservative/fertility-sparing approaches to extirpative therapy. Consistently, successful outcomes often are predicated on correctly identifying the abnormal peripheral pain process (which often is only part of the complete picture for these patients). Further research is needed to better guide clinicians as to when to choose surgical therapy vs. targeting secondary contributors to pelvic pain.